2022
DOI: 10.3389/fphar.2022.900551
|View full text |Cite
|
Sign up to set email alerts
|

An Overview of the Protein Binding of Cephalosporins in Human Body Fluids: A Systematic Review

Abstract: Introduction: Protein binding can diminish the pharmacological effect of beta-lactam antibiotics. Only the free fraction has an antibacterial effect. The aim of this systematic literature review was to give an overview of the current knowledge of protein binding of cephalosporins in human body fluids as well as to describe patient characteristics influencing the level of protein binding.Method: A systematic literature search was performed in Embase, Medline ALL, Web of Science Core Collection and the Cochrane … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 123 publications
0
8
0
Order By: Relevance
“…Additionally, the degree of inflammation affects free drug concentrations in the CSF due to the higher protein content during infection and may reduce bactericidal effects [ 49 , 50 ]. Despite that, highly protein bound drugs, such as ceftriaxone, were found to have a significantly lower rate of protein binding in the CSF compared to serum (CSF 18.8% ± 6.21% vs. serum 32.3% to 95%); this effect may be due to a saturation of binding sites when higher doses are utilized [ 51 , 52 ].…”
Section: Beta-lactam Antibioticsmentioning
confidence: 99%
“…Additionally, the degree of inflammation affects free drug concentrations in the CSF due to the higher protein content during infection and may reduce bactericidal effects [ 49 , 50 ]. Despite that, highly protein bound drugs, such as ceftriaxone, were found to have a significantly lower rate of protein binding in the CSF compared to serum (CSF 18.8% ± 6.21% vs. serum 32.3% to 95%); this effect may be due to a saturation of binding sites when higher doses are utilized [ 51 , 52 ].…”
Section: Beta-lactam Antibioticsmentioning
confidence: 99%
“…Hypoalbuminemia is present in 40–50% of critically ill patients and may be associated with an increased free fraction of highly protein-bound beta-lactams [ 27 , 31 ]. Apart from ceftazidime, cefotaxime and cefepime, most cephalosporins exhibit high binding to plasma proteins [ 35 ]. A high level of protein-binding was first described in penicillin and carbapenems and later in ertapenem and derivates of oxacillin [ 15 , 36 ].…”
Section: Consideration In Patients With Hypoalbuminemiamentioning
confidence: 99%
“…The results of the systemic review of studies dedicated to PPB of different cephalosporines revealed a high rate of variability of binding patterns considering different fluids and different categories of patients [ 140 ]. The highest rates of protein binding in plasma and serum of adults were detected for cefonicid (mean 82–98%, four studies), and cefoperazone (mean 89–92%, four studies).…”
Section: General Considerations On Neonate’s Pharmacokineticsmentioning
confidence: 99%
“…The highest rates of protein binding in plasma and serum of adults were detected for cefonicid (mean 82–98%, four studies), and cefoperazone (mean 89–92%, four studies). The lowest protein binding rates were demonstrated for cefuroxime (mean 16–33%, five studies), cefotaxime (mean 8–41%, four studies), and ceftazidime (mean 0–21%, six studies) [ 140 ]. Estimating concentration ranges authors revealed a linear pattern of protein binding for the next cephalosporines: ceforanide, cefamandole, cefmenoxime, cefotaxime, cefluprenam, cefotetan, and cefoxitin.…”
Section: General Considerations On Neonate’s Pharmacokineticsmentioning
confidence: 99%
See 1 more Smart Citation